The Influence of social media on the Mental Health and Self-esteem among Budding Management Students: A Comprehensive Study - Dr. Viswanath Bandi; T. Ashwini Reddy (The Bioscan, 2024)
Purpose: social media helps students connect, collaborate, and build digital skills, enriching their learning experience up to a point. In this regard, our research study aimed to investigate the impact of social media on the mental health and self-esteem of budding management students. Design/methodology/approach: We have conducted extensive literature search and based on the reviews, we have arrived at the conceptual framework and survey questionnaire, thereby ensuring all the variables are covered. To assess mental health we have integrated our questionnaire with GAD-7, PHQ-9 scales and for self-esteem we have used Rosenberg Questionnaire. The questionnaire was shared to around 50 students of 3rd BBA in the form of google form for their responses. We used MS EXCEL TOOLs to analyze the data, providing insights. Findings: Our research showed that social media had an impact on the mental health of these budding management students (BBA 3rd Year) with very low intensity of anxiety as per GAD-7 scale indicating higher maturity levels. When it comes to self-esteem, our research also showed that social media does not have any impact on the self-esteem of the respondents except for social media platform selection. Practical implications: Mental Health is key for good health and academic performance of the students which further enhances self-esteem among students in the form of confidence. We suggest students to view selected media platform for information purpose and relaxation purpose for a specific short duration which is fixed per day avoid falling in to the trap of anxiety curve (as currently low anxiety) for leading a high QoL beyond academics.